Influencing Ink: A web documentary - Abella, Jacob Emmanuel Bukid (Animo Repository, 2023)
The culture of tattoo in the Philippines is starting to gain widespread popularity by way of how its common perceptions have been shifting in the younger generations. As the aesthetics and practice of tattooing become more prevalent in social media today, individuals have started to become more exposed to, educated and interested in experiencing the tattoo culture. Influencing Ink is a web documentary that comprises 5 episodes, showcasing the perspective of different tattoo artists and their experiences of how social media has affected their careers for the better within a culture that was once seen as taboo. Throughout the process, the proponents were able to engage in meaningful conversations with the artists to learn more about how they began their careers and personal experiences within a stigmatized industry. Within the larger story, Influencing Ink conveys the message of how powerful communication can be with the rise of mediatization as exemplified by social media and its ability to influence the lives of individuals who thought that their careers would not climax. Featuring tattoo artists Oben Miralles, Maan Simbajon, Dyani Lao, Yok Genabe, and Crimson River Tattoo Artists (Gigie, Wiji, and Annie), the web documentary offers five different perspectives of how tattoo culture has shifted in the Philippine scenario These artists have been in the industry for more than 5 years - some even 10 years — and have first-hand experience on the transition of their careers by way of social media. The episodes will be showcased within a website for viewers to freely choose the sequence of the episodes — ultimately lending each viewer a different viewing experience. YouTube links to each episode will also be embedded in the website for easier accessibility.